Novel Cleaning-in-Place Strategies for Pharmaceutical Hot Melt Extrusion - Martin Spoerk; Ioannis Koutsamanis; Josip Matić; Simone Eder; Carolina Patricia Alva Zúñiga; Johannes Poms; Jesús Alberto Afonso Urich; Raymar Andreína Lara García; Klaus Nickisch; Karin Eggenreich; Andreas Berghaus; Kathrin Reusch; et al. (MDPI AG, 2020)
To avoid any type of cross-contamination, residue-free production equipment is of utmost importance in the pharmaceutical industry. The equipment cleaning for continuous processes such as hot melt extrusion (HME), which has recently gained popularity in pharmaceutical applications, necessitates extensive manual labour and costs. The present work tackles the HME cleaning issue by investigating two cleaning strategies following the extrusion of polymeric formulations of a hormonal drug and for a sustained release formulation of a poorly soluble drug. First, an in-line quantification by means of UV-Vis spectroscopy was successfully implemented to assess very low active pharmaceutical ingredient (API) concentrations in the extrudates during a cleaning procedure for the first time. Secondly, a novel in-situ solvent-based cleaning approach was developed and its usability was evaluated and compared to a polymer-based cleaning sequence. Comparing the in-line data to typical swab and rinse tests of the process equipment indicated that inaccessible parts of the equipment were still contaminated after the polymer-based cleaning procedure, although no API was detected in the extrudate. Nevertheless, the novel solvent-based cleaning approach proved to be suitable for removing API residue from the majority of problematic equipment parts and can potentially enable a full API cleaning-in-place of a pharmaceutical extruder for the first time.